Virtual property : towards a general theory - Pałka, Przemysław (European University Institute, 2017)
The primary contribution of the thesis is a theory enhancing the legal understanding of the phenomenon of virtual property, encompassing presentation of data and a new conceptual framework to interpret it. The author argues that the normative debates concerning the phenomenon have underestimated the importance of understanding and conceptualizing it first, and aims at amending this gap. The ‘virtual property phenomenon’ refers to the users of internet platforms and online computer games ‘possessing’ virtual items – digital objects that exist within these services – and getting into economic and social relations concerning these items, with other users, service providers and third parties. These relations are regulated by different types of service-specific rules – contractual and the ‘code’ – created unilaterally by the service providers, who additionally retain the ability to interpret and enforce them, using ‘digital force’, i.e. by modifying and deleting virtual items, and blocking users’ accounts. The primary challenge stems not from the fact that the phenomenon is not regulated, but from the fact that lawyers lack words – terms and concepts – to even conduct a meaningful debate about it, or how to respond to it. The thesis consists of six chapters. Firstly, the author describes the phenomenon and analyzes the theoretical and regulatory legal challenges posed by its emergence. Secondly, he critically assesses the state of the art. Thirdly, a methodology to address these challenges is proposed, which can also be used in other research projects concerning law and technology. Fourthly, the author explains how the process of digitalization has fundamentally challenged the assumptions that private law held about the structure of reality, and proposes new doctrinal tools to conceptualize it. Fifthly, the author presents a legally useful concept of virtual items, and argues that granting users property rights over them might not be the optimal means of realizing the property goals. Finally, the author proposes a normative solution, a correction of private law, responding to the new type of inequality in relations, namely a user protection law.
Keywords: Computer games; Internet; Possession (Law); Property

Libraries in the digital renaissance law and policy for book digitization - Panezi, Argyri (European University Institute, 2017)
This dissertation examines the phenomenon of book digitization and the legal challenges for the creation of digital libraries. It explores whether the current copyright framework supports libraries in the digital era as they strive to remain the institutional guardians of our literary treasures. The thesis hypothesis is that the current framework is unsuccessful or inadequate in supporting libraries. To test this hypothesis and identify the legal inefficacies the dissertation examines context, i.e. the history and rationale for applying copyright rules to books and libraries, the copyright rules as applied to libraries before and after digitization was possible, various digitization projects and the practical challenges that digitization brought about, and, the relevant litigation which has started on both sides of the Atlantic covering over a decade now. Furthermore, the thesis explores normative directions of copyright rules, including their exceptions, applicable to libraries in the digital era. It ultimately proposes that among various players claiming this role, libraries, given their institutional functions and capabilities, should be attributed rights to digitization and a favorable legal framework for providing access to digital material.
Keywords: Copyright; Digital libraries; Electronic data processing; Electronic information resources; Intellectual property; Propriedade intelectual; Propriété intellectuelle